The Triad Divided: A Curvilinear Mediation Model Linking Founder Machiavellianism, Narcissism, and Psychopathy to New Venture Performance - Brownell, Katrina M.; Quinn, Audra; Bolinger, Mark T. (Entrepreneurship Theory and Practice, 2024)
Across two studies, we apply self-regulation theory to test nonlinear relationships between founder Machiavellianism, narcissism, and psychopathy and new venture performance. Our hypotheses are supported for Machiavellianism and psychopathy, but contrary to our theorizing, we find a positive relationship between narcissism and performance. Furthermore, we identify an important explanatory mechanism in knowledge sharing, which mediates the curvilinear relationships at moderate and high levels. Our research has implications for how we understand the influence of problematic founder personality traits and how behavioral differences at varying levels of these traits can explain relationships with performance, and it presents a nuanced perspective to trait-based explanations for destructive entrepreneurial actions.